Hearing function after betahistine therapy in patients with Ménière's disease - Seyed Javad Seyed Tootoonchi (Brazilian Journal of Otorhinolaryngology, 2016)
Introduction: Preventing or reversing hearing loss is challenging in Ménière’s disease. Betahistine, as a histamine agonist, has been tried in controlling vertigo in patients with Ménière’s disease, but its effectiveness on hearing problems is not known. Objective: To examine the effect of betahistine on hearing function in not-previously-treated patients with Ménière’s disease and to define possible contributors in this regard. Methods: A total of 200 not-previously-treated patients with definite unilateral Ménière’s disease received betahistine by mouth (initial dose, 16 mg three times a day; maintenance dose, 24---48 mg daily in divided doses). Changes in indicators of hearing status before and six months after treatment were documented. Hearing loss was considered as the mean hearing level >25 dB HL at five frequencies. Results: The mean duration of disease was 3.37 years. Six months after treatment the mean hearing level decreased by 6.35 dB compared to that at the baseline (p < 0.001). Both patients’ age and the duration of disease correlated negatively with the improvement in hearing function. Post treatment hearing loss was independently associated with age, the initial hearing level and the chronicity of disease. The corresponding optimal cut-off points for predicating a persistent hearing loss 6 months after treatment were 47 years, 38 dB HL, and 1.4 years, respectively. Conclusion: Oral betahistine was significantly effective in preventing/reversing hearing deterioration in patients with Ménière’s disease. Age, the hearing level on admission, and the disease duration were independent predictors of hearing status after treatment.